1977
DOI: 10.1113/jphysiol.1977.sp012025
|View full text |Cite
|
Sign up to set email alerts
|

Differential enhancement of early and late components of the cerebral somatosensory evoked potentials during forced‐paced cognitive tasks in man

Abstract: SUMMARY1. Cerebral potentials evoked by random sequences of electrical stimuli to four fingers were recorded in intact man performing selective attention tasks. Eye movements and other artifacts were excluded from the averaged traces. Different finger stimuli were designated as targets to be mentally counted in alternate runs of each experiment. The high mean random rate of stimuli (Il10/min) fully involved the processing capacities of the subject. Vigilance changes or differential expectancy effects were excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
0
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(126 citation statements)
references
References 43 publications
13
112
0
1
Order By: Relevance
“…Electrical stimulation of the me&an and ulnar nerves at the wrist evoked similar latency SEP (Fig 1) 'thalamocortical" N20 peaked at 18 4 ± 1 2 msec and 18 8 + 1 2 msec respectively, cortical P27 peaked at 22 7+18 msec and 22 4+13 msec respectively (see Emerson and Pedley 1984 for a dxscussxon of origins of these components) Electrical sumulauon of digits 1-2 and 5 evoked the same sequence of components but at approximately 3 msec longer latencles, N20 peaked at 21 8 _+ 0 8 msec and 21 7 ± 0 8 msec respectively, P27 peaked at 25 3 ± 1 7 msec and 25 2+ 1 3 msec respectively The peripheral nerve afferent volleys and N20 components to the different stimuli figure) and ulnar (bottom half of figure) nerve stimulation The thalamocortlcal N20 and cortical P27 components are labeled Note that the P27 component of SEP to me&an nerve sumulatlon was attenuated dunng digit 1 movement (upper traces) whereas the P27 component of the SEP to ulnar nerve stimulation was most attenuated during dig~t 5 movement (lov~er traces) The peripheral nerve potentials evoked by these stimuli did not change dunng these movements The bar graphs plot the attenuation of the P27 component dunng median nerve stimulation (upper portion) and ulnar nerve stimulation (lower portion) a, a funcuon of the finger that x~as moxed did not significantly change dunng any movement condition (Tables I and II) In contrast, the P27 component was attenuated dunng certain combinations of movements and nerve stimulation Opposition of the thumb towards digit 5 was accompanied by attenuation of potentials evoked by both median nerve and &git 1-2 stimulation (P27 dlrmnlshed to 35 67 ± 27 10% and to 44 75_+ 10 50% respectively, P < 0 01 Fig 1 top section, digit 1 movement, and Table I left-hand columns) In contrast, potentials evoked by both ulnar ~erve and digit 5 stimulation were not significantly affected during thas same digit 1 movement (Fig 1 bottom section, Table I right-hand columns) Abduction of the fifth finger was accompanied by attenuation of potentials evoked by both ulnar nerve and digit 5 stimulauon (P27 dxlmmshed to 31 80+7 29% and to 37 00± 12 36% respectively, P < 0 01, Fig 1 bottom section, digit 5 movement, and Table II right-hand columns) In contrast, potentials evoked by both median nerve and dtgits 1-2 stimulation were not significantly affected dunng this fifth digit movement (Fig 1 top section and Table II left columns) Attenuation of SEP IS not due to changes in subject vigI- lance and attention since the alterations in SEP were speofic only for certain combinations of nerve stimulation and movement conditions Moreover, the earhest task-related change in SEP that has been reported affects those components with latencles longer than 55 msec (Desmedt and Robertson 1977) Discussion It has been amply demonstrated that there is an attenuauon of SEP during movement of the stimulated limb in both animals and humans (Ghez and Plsa 1972, Papakostopoulos et al 1975…”
Section: Resultsmentioning
confidence: 71%
“…Electrical stimulation of the me&an and ulnar nerves at the wrist evoked similar latency SEP (Fig 1) 'thalamocortical" N20 peaked at 18 4 ± 1 2 msec and 18 8 + 1 2 msec respectively, cortical P27 peaked at 22 7+18 msec and 22 4+13 msec respectively (see Emerson and Pedley 1984 for a dxscussxon of origins of these components) Electrical sumulauon of digits 1-2 and 5 evoked the same sequence of components but at approximately 3 msec longer latencles, N20 peaked at 21 8 _+ 0 8 msec and 21 7 ± 0 8 msec respectively, P27 peaked at 25 3 ± 1 7 msec and 25 2+ 1 3 msec respectively The peripheral nerve afferent volleys and N20 components to the different stimuli figure) and ulnar (bottom half of figure) nerve stimulation The thalamocortlcal N20 and cortical P27 components are labeled Note that the P27 component of SEP to me&an nerve sumulatlon was attenuated dunng digit 1 movement (upper traces) whereas the P27 component of the SEP to ulnar nerve stimulation was most attenuated during dig~t 5 movement (lov~er traces) The peripheral nerve potentials evoked by these stimuli did not change dunng these movements The bar graphs plot the attenuation of the P27 component dunng median nerve stimulation (upper portion) and ulnar nerve stimulation (lower portion) a, a funcuon of the finger that x~as moxed did not significantly change dunng any movement condition (Tables I and II) In contrast, the P27 component was attenuated dunng certain combinations of movements and nerve stimulation Opposition of the thumb towards digit 5 was accompanied by attenuation of potentials evoked by both median nerve and &git 1-2 stimulation (P27 dlrmnlshed to 35 67 ± 27 10% and to 44 75_+ 10 50% respectively, P < 0 01 Fig 1 top section, digit 1 movement, and Table I left-hand columns) In contrast, potentials evoked by both ulnar ~erve and digit 5 stimulation were not significantly affected during thas same digit 1 movement (Fig 1 bottom section, Table I right-hand columns) Abduction of the fifth finger was accompanied by attenuation of potentials evoked by both ulnar nerve and digit 5 stimulauon (P27 dxlmmshed to 31 80+7 29% and to 37 00± 12 36% respectively, P < 0 01, Fig 1 bottom section, digit 5 movement, and Table II right-hand columns) In contrast, potentials evoked by both median nerve and dtgits 1-2 stimulation were not significantly affected dunng this fifth digit movement (Fig 1 top section and Table II left columns) Attenuation of SEP IS not due to changes in subject vigI- lance and attention since the alterations in SEP were speofic only for certain combinations of nerve stimulation and movement conditions Moreover, the earhest task-related change in SEP that has been reported affects those components with latencles longer than 55 msec (Desmedt and Robertson 1977) Discussion It has been amply demonstrated that there is an attenuauon of SEP during movement of the stimulated limb in both animals and humans (Ghez and Plsa 1972, Papakostopoulos et al 1975…”
Section: Resultsmentioning
confidence: 71%
“…Some previous studies have shown effects of spatial attention overlapping with N80 when the hands were positioned in front space or by the side of the body (e.g. Desmedt and Robertson 1977;Hötting et al 2003;Michie et al 1987;Schubert et al 2008). In these studies attention to the hands was sustained, however, which is thought to give rise to earlier ERP modulations than cueing attention on a trial-by-trial basis like in the present study because attention may be focused more efficiently when it is maintained on one location (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These components are thought to be associated with processing in numerous areas including secondary somatosensory cortex and bilateral frontal and parietal regions (e.g. Allison et al 1989;De Santis et al 2007;Desmedt and Robertson 1977;Hari et al 1984;Mima et al 1998). Previous studies have shown effects of hand distance (Eimer et al 2004;Gillmeister et al 2010a) and of vision of the hands (Sambo et al 2009) on modulations reflecting transient attentional selection between the hands in the P100-N140 time range.…”
Section: Discussionmentioning
confidence: 99%
“…Although some of the earlier studies suggested the pre-cortical modulation of sensory signals by attention (Eason, Harter & White, 1969;Hernandez-Peon, 1967) recent studies show that the attention-induced enhancement of sensory evoked potentials occurs mostly after the presumed first cortical events (Hillyard & Picton, 1987;Desmedt & Robertson, 1977).…”
Section: Attention Has Influence On Relatively Early Stages In Visualmentioning
confidence: 99%